Age differences in the prosocial influence effect. Issue 6 (15th April 2018) - Foulkes, Lucy; Leung, Jovita T; Fuhrmann, Delia; Knoll, Lisa J; Blakemore, Sarah‐Jayne
Abstract: Social influence occurs when an individual's thoughts or behaviours are affected by other people. There are significant age effects on susceptibility to social influence, typically a decline from childhood to adulthood. Most research has focused on negative aspects of social influence, such as peer influence on risky behaviour, particularly in adolescence. The current study investigated the impact of social influence on the reporting of prosocial behaviour (any act intended to help another person). In this study, 755 participants aged 8–59 completed a computerized task in which they rated how likely they would be to engage in a prosocial behaviour. Afterwards, they were told the average rating (in fact fictitious) that other participants had given to the same question, and then were asked to rate the same behaviour again. We found that participants' age affected the extent to which they were influenced by other people: children (8–11 years), young adolescents (12–14 years) and mid‐adolescents (15–18 years) all significantly changed their ratings, while young adults (19–25 years) and adults (26–59 years) did not. Across the three youngest age groups, children showed the most susceptibility to prosocial influence, changing their reporting of prosocial behaviour the most. The study provides evidence that younger people's increased susceptibility to social influence can have positive outcomes. Abstract : Blurb: Prosocial influence is defined here as the tendency to report more prosocial behaviour as the result of reading about this behaviour in others. Our study of 8‐59 year olds (N=755) found that children and adolescents show more prosocial influence than adults, suggesting that young people's susceptibility to social influence can have positive outcomes.